Reduced CD5(+)CD24(hi)CD38(hi) and interleukin-10(+) regulatory B cells in active anti-neutrophil cytoplasmic autoantibody-associated vasculitis permit increased circulating autoantibodies - Aybar, L T (Clin Exp Immunol, 2015)
Pathogenesis of anti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis is B cell-dependent, although how particular B cell subsets modulate immunopathogenesis remains unknown. Although their phenotype remains controversial, regulatory B cells (B(regs)), play a role in immunological tolerance via interleukin (IL)-10. Putative CD19(+)CD24(hi)CD38(hi) and CD19(+)CD24(hi)CD27(+) B(regs) were evaluated in addition to their CD5(+) subsets in 69 patients with ANCA-associated vasculitis (AAV). B cell IL-10 was verified by flow cytometry following culture with CD40 ligand and cytosine–phosphate–guanosine (CpG) DNA. Patients with active disease had decreased levels of CD5(+)CD24(hi)CD38(hi) B cells and IL-10(+) B cells compared to patients in remission and healthy controls (HCs). As IL-10(+) and CD5(+)CD24(hi)CD38(hi) B cells normalized in remission within an individual, ANCA titres decreased. The CD5(+) subset of CD24(hi)CD38(hi) B cells decreases in active disease and rebounds during remission similarly to IL-10-producing B cells. Moreover, CD5(+) B cells are enriched in the ability to produce IL-10 compared to CD5(neg) B cells. Together these results suggest that CD5 may identify functional IL-10-producing B(regs). The malfunction of B(regs) during active disease due to reduced IL-10 expression may thus permit ANCA production.